Determining the Role of the Ethanolic Leaf Extract of Diodia sarmentosa as a Free Radical Scavenger, and an Antioxidant in High Fat Diet Fed Wistar Rats - Stephen Chinedumije Korie; Tobias I. Ndubuisi Ezejiofor (New Visions in Biological Science Vol. 5, 2021)
Diodia sarmentosa (Sw) also known as Zimbabwe flora or Tropical button weed is a straggling or procumbent perennial herb that grows in evergreen forest, riverine vegetation and bush land. Traditionally, it has been used for the treatment of different ailments like ulcer and diabetes. This study investigated the role of the ethanolic leaf extract of Diodia sarmentosa as a free radical scavenger, and an antioxidant in high fat diet fed wistar rats. The objectives of this study are; To determine the plant extract’s ability to scavenge free radicals in vitro, and to ascertain in vivo if the plant extract can boost antioxidant activities and lower lipid peroxidation. In this study, thirty (30) male wistar rats (150 g-200 g) were divided into five (5) groups: Negative control rats, Positive control rats, Low dose extract rats treated with 250 mg/kg, High dose extract rats treated with 500mg/kg of the extract, and standard antihyperlipidaemic drug rats treated with 5 mg/kg of Simvastatin. High fat diet was fed to the rats using Ghee and Coconut oil in the ratio of 3:1 for six (6) weeks, and administration of the treatments commenced after the 3rd week till the 6th week. The role of Diodia sarmentosa as a free radical scavenger and an antioxidant was ascertained by assessing parameters like nitric oxide radical, hydroxyl radical, malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione S-transferase (GST) in the serum of the test rats. Diodia sarmentosa scavenged free radicals In vitro by inhibiting nitric oxide and hydroxyl radicals in a concentration-dependent manner, thus showing an inhibitory concentration at 50% (IC50) of 907.17 \(μ\)g/ml \(±\) 45.36 and 2173.44 \(μ\)g/ml \(±\) 100.11 respectively. Results from this study showed that antioxidant enzymes like SOD, GPx and CAT in the serum of the test rats were significantly increased (p<0.05) by both doses of the extract when compared to the PC group, and its effect similar to the standard drug (Simvastatin) used. GST activity was decreased in the serum of the test rats by both doses of the extract, however this decrease was not significant (p>0.05). Lastly, the measure of lipid peroxidation i.e malondialdehyde level was significantly decreased (p<0.05) by both doses of the extract in the serum of the tests rats. Conclusively, Diodia sarmentosa has antioxidant potentials on account of its potentiality to scavenge free radicals, replenish antioxidant enzymes and reduce lipid peroxidation.